Analisis Pengungkapan Keberlanjutan Keuangan Berbasis Website pada Universitas Islam Negeri di Indonesia - Sri Ardriani; Agusdiwana Suarni; Masrullah Masrullah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The importance of transparency and accountability through digital media is the main reason for this research, considering that websites are a crucial tool for universities in building their image and communicating their social responsibility to the public. This study aims to analyze the level of website-based financial visits at State Islamic Universities (UIN) in Indonesia through the perspectives of Stakeholder Theory and Signaling Theory. The method used is descriptive quantitative with a population of all State Islamic Universities (PTAIN) under the auspices of the Indonesian Ministry of Religious Affairs, where 35 UINs were selected as samples using a purposive sampling technique. Data were collected through observation of website content based on the Global Reporting Initiative (GRI) standard indicators. The results show that although most UINs have official websites as their main information media, the overall transmission rate is still at an average of 46.91% (categorized as poor). Specifically, the social aspect received the highest score (58.68%), followed by the economic aspect (54.49%), while the environmental aspect was the lowest (27.56%). The findings indicate low accessibility of formal reports, with only UIN Sulthan Thaha Saifuddin Jambi having published a structured sustainability report, and only UIN K.H. Saifuddin Zuhri Purwokerto providing publicly available financial reports. These low figures suggest that Islamic higher education institutions in Indonesia have not yet optimally utilized digital platforms for permit reporting. These findings serve as important evaluation material for university administrators to strengthen digital information governance to increase stakeholder trust.